A concept to Reduce Idle Time on Stevedoring Activities in a Container Terminal - Nurul Khafid; Bambang Syairudin (IPTEK Journal of Proceedings Series, 2019)
The flow of goods is still dominated by sea transport compared with other modes of transport so that the container terminal is very important role in the economic system of a country. The main indicator of performance of a container terminal is the total container throughput in TEUs per year. Recording is done in the process of stevedoring activities. It was found that the idle container cranes (CC) increases higher than the increase in throughput that is 77% compared with 22%. This should not apply instead. Waiting for a load and Combined Terminal Tractor (CTT) / truck are the largest contributor to the idle CC. No one can be sure that the cargo does not exist because there is no CTT which brings, or the container is not ready. The results showed that by changing the arrangement of CC and CTT obtained the increase in number of containers underserved. Another result is a decrease in the average number of ships that was rejected due to full berth and unloading equipment utilization